Partisipasi Penyusunan Anggaran Pada Budgetary Slack dengan Komitmen Organisasi, Opportunistic Behavior, dan Ketidakpastian Lingkungan Sebagai Variabel Moderasi - Negara, Putu Ryan Sutha; Wirajaya, I Gde Ary (E-Jurnal Akuntansi; Vol 22 No 3 (2018), 2018)
Public sector budgeting is an accountability instrument for public funds management and the implementation of programs financed by public money for the welfare of the people. The enactment of regional autonomy has led to changes in local financial management into a performance-based budget model through participation in budgeting. This study aims to examine empirical evidence of organizational commitment, opportunistic behavior and environmental uncertainty as moderating variables influence of budget participation on budgetary slack. This research was conducted at Organization of Jembrana District. The number of samples were 143 people using non probability sampling technique with purposive sampling approach. Methods of data collection conducted by survey method using a questionnaire. Data analysis technique used is test of Moderating Regression Analysis (MRA). Based on th is research’s result , it ’ s known that organizational commitment variable and environmental uncertainty have an effect on budgetary slack, while opportunistic behavior has no effect on budgetary slack. Keywords: budgeting participation, budgetary slack, organizational commitment, opportunistic behavior, environmental uncertainty